2016
DOI: 10.1177/1464884916667873
|View full text |Cite
|
Sign up to set email alerts
|

Journalistic transformation: How source texts are turned into news stories

Abstract: In the scholarly debate, ideals of original reporting are commonly contrasted against the churnalistic reproduction of source content. However, most news making lies between these poles: Journalists rely on but transform the available source material, renegotiating its original meaning. In this article, we define journalistic transformation as those interventions journalists make in their use of third-party textual material in the pursuit of crafting a news story. Journalists (1) select contents from available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…For instance, we can only detect if explicit references are made in the news to doubt, or positive and negative evaluations. However, many journalistic distancing and evaluation practices rely on implicit connotations, narrative arrangements, and other more subtle techniques (Tenenboim-Weinblatt and Baden, 2016). Likewise, while we capture a complex and large range of references to available sources and groups, we cannot distinguish whether these are being covered as passive objects (possibly, in a hostile manner), or allowed to speak and present their views in the coverage (Baden and Springer, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we can only detect if explicit references are made in the news to doubt, or positive and negative evaluations. However, many journalistic distancing and evaluation practices rely on implicit connotations, narrative arrangements, and other more subtle techniques (Tenenboim-Weinblatt and Baden, 2016). Likewise, while we capture a complex and large range of references to available sources and groups, we cannot distinguish whether these are being covered as passive objects (possibly, in a hostile manner), or allowed to speak and present their views in the coverage (Baden and Springer, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Proceeding in a highly case-bound fashion, most accounts of media influences are based on thick descriptions and argumentation, highlighting selected routes of media influence. Comparative assessments or other strategies able to control the complex confounding explanations for observed phenomena in each case have been rare, as have been efforts at testing hypotheses or identifying the specific conditions and factors enabling or obstructing specific influences (Fröhlich et al, 2007; Tenenboim-Weinblatt et al, 2016; Neuman, 1996). Moreover, most studies focus on single types of media, addressing influences of highbrow journalism, global social media, or specific regional radio stations.…”
Section: Theory Design and Methodsmentioning
confidence: 99%
“…The Israeli media quickly translated and published these reports, although in retrospect some of the publications turned out to be untrue. Therefore, when journalists use information coming from the media on the other side of the conflict, they usually use distancing words or doubtful reporting verbs (Tenenboim‐Weinblatt & Baden, ). In other cases, before the photography crew arrives at the scene of events, TV channels are collecting soundbites and pictures that were aired in other media, especially global ones (Orgad, ).…”
Section: Types Of Media Sources Journalists Use During Conflictsmentioning
confidence: 99%
“…After selecting contents from these sources, journalists arrange, summarize, edit, and shape the information into a story that serves their purposes and is tailored to their audiences. They use a variety of methods, such as highlighting/omission of information, reinforcing/blurring political attitudes, linking information to the identity of the collective, using descriptive words to evoke emotional responses, and adding background and additional sources (Tenenboim‐Weinblatt & Baden, ). Focusing on the Israeli–Palestinian conflict, Baden and Tenenboim‐Weinblatt () found that by using these “transformations,” journalists tend to reframe selected source frames in a way that interferes with the sources' ability to insert their claims and interpretations into the news stories.…”
Section: Types Of Media Sources Journalists Use During Conflictsmentioning
confidence: 99%